Long-Term Administration of High-Fat Diet Corrects Abnormal Bone Remodeling in the Tibiae of Interleukin-6-Deficient Mice. (January 2016) - Feng, Wei; Liu, Bo; Liu, Di; Hasegawa, Tomoka; Wang, Wei; Han, Xiuchun; Cui, Jian; Yimin,; Oda, Kimimitsu; Amizuka, Norio; Li, Minqi
In this study, we aimed to evaluate the influence of diet-induced obesity on IL-6 deficiency-induced bone remodeling abnormality. Seven-week-old IL-6 -/- mice and their wild type (WT) littermates were fed a standard diet (SD) or high-fat diet (HFD) for 25 weeks. Lipid formation and bone metabolism in mice tibiae were investigated by histochemical analysis. Both IL-6 -/- and WT mice fed the HFD showed notable body weight gain, thickened cortical bones, and adipose accumulation in the bone marrow. Notably, the HFD normalized the bone phenotype of IL-6 -/- mice to that of their WT counterpart, as characterized by a decrease in bone mass and the presence of an obliquely arranged, plate-like morphology in the trabecular bone. Alkaline phosphatase and osteocalcin expressions were attenuated in both genotypes after HFD feeding, especially for the IL-6 -/- mice. Meanwhile, tartrate-resistant acid phosphatase staining was inhibited, osteoclast apoptosis rate down-regulated (revealed by TUNEL assay), and the proportion of cathepsin K (CK)-positive osteoclasts significantly increased in IL-6 -/- mice on a HFD as compared with IL-6 -/- mice on standard chow. Our results demonstrate that HFD-induced obesity reverses IL-6 deficiency-associated bone metabolic disorders by suppressing osteoblast activity, upregulating osteoclastic activity, and inhibiting osteoclast apoptosis.